STUDY OF THE EFFECT OF SOME ALKALOIDS ON THE CONTRACTILE ACTIVITY OF AORTIC SMOOTH MUSCLE CELLS - Mirzayeva Yulduzkhon Takhirjonovna (Western European Studies, 2024)
Ca2+ ions play a leading role in regulation of contractile and functional activity of cardiac muscles and smooth muscles of blood vessels, which ensure normal activity of cardiovascular system as a whole [1]. In this regard, disturbances in the regulation of Ca 2+ homeostasis are the main cause of pathogenesis of a number of diseases of the cardiovascular system, including heart failure, arrhythmias, myocardial infarction, hypertension and strokes [2]. Therefore, one of the most urgent tasks of modern biophysics, pharmacology and medicine is to study and characterize the mechanisms of pharmacological regulation of Ca2+ -homeostasis and Ca2+ -transporting systems of cardiac and smooth muscles providing its maintenance. The aim of the work was to study the effect of 1-O-acetylkarakoline, a derivative of the diterpenoid alkaloid karakolin, isolated from the plant Aconitum karakolicum, on the contractile activity of smooth muscle cells (SMC) of the rat aorta. Karakolin has a pronounced antiarrhythmic effect, which is determined by the presence of specific functionally important groups in its structure [3]. Thus, the replacement of the OH-group at the carbon atom C-1 of the lycoketonin skeleton of Karakolin with an acetyl group (Fig. 1) leads to a significant increase in antiarrhythmic activity of 1-O-acetylkarakoline [4].
Keywords: smooth muscle; sarcoplasmic reticulum; aorta; phenylephrine